The Use of Shared Reading Strategy in Teaching Reading Comprehension at SMPN 1 Bulukumba - Rizky Thurfah Wiradyaningsih; Chairil Anwar Korompot; Geminastiti Sakkir (Journal of Excellence in English Language Education, 2022)
The purpose of this study was to determine whether the Shared Reading Strategy (SRS) had an effect or not on students' reading comprehension. This research is a pre-experimental study involving one group pre-test and post-test. This research took place in Bulukumba in the 2021/2022 academic year. The sample of this research is the ninth-grade students of SMPN 1 Bulukumba. The researchers used a total sampling technique in selecting a sample consisting of 25 students as respondents. This research uses quantitative methods. The researchers used the reading test as a research instrument. The data collection technique is to give students a reading test in the form of pre-test and post-test. The results of students' reading comprehension scores from pre-test to post- test showed a significant difference. It was found that Sig.(2-tailed) was 0.000 < 0.05. The results showed that the average value of the pretest was 63.65 with a standard deviation of 7.81, while the average value of the post-test was 76.34 with a standard deviation of 9.54. This means that there is an effect on the application of the Shared Reading Strategy in learning to read comprehension for the students of SMPN 1 Bulukumba.